Managing migration through quotas: An option-theory perspective - Michele Moretto; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2008)
Recent European Legislation on immigration has revealed a particular paradox on migration policies. On the one hand, the trend of recent legislation points to the increasing closure of frontiers (OECD 1999, 2001,2004), also by using immigration quotas. On the other hand, there is an increase of regularization, i.e., European policies are becoming less tight. Our aim here is to study these counterbalanced and opposite policies in European immigration legislation in a unified framework . To do this, we have used a real option approach to migration choice that assumes that the decision to migrate can be described as an irreversible investment decision where quotas represent an upper bound limit. Our results show that the paradox of counterbalancing immigration policies is not odd but it could be in line with an optimal policy to control migration inflow. In particular, we show that if the government controls the information related to the immigration quota system it could delay the mass entry of immigrants maintaining, in the long run, the required immigration stock and controlling the flows in the short-run.
Keywords: F22; J61; O15; R23; 330; Immigration; Real Option; Quota System